2019
DOI: 10.1002/jcp.28288
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin relieves LPS‐induced mastitis by inhibiting inflammatory response and repairing the blood–milk barrier

Abstract: Mastitis, an inflammation of mammary gland, is a serious disease that affects the health of dairy cows around the world. Myricetin, a flavonoid from Bayberry, has been reported to suppress various inflammatory response. The aim of this study was to evaluate the effect of myricetin on lipopolysaccharide (LPS)‐induced in vivo and in vitro mastitis model and clarify the underlying mechanism. In vivo experiments, myricetin attenuated the severity of inflammatory lesion and neutrophil infiltration. Moreover, myrice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 37 publications
4
45
0
1
Order By: Relevance
“…Similarly, study showed that adding LAB prevented E. coli infection and depressed the expression of proinflammation cytokine IL-8 and IL-1β of endometrial cells in vitro (Genis et al 2016). MPO activity is a quantitative assessment of neutrophil infiltration into mammary gland (Kan et al 2019), and our result showed that milk activity of MPO was significantly decreased by supplementation of yeast, LAB or the mixture. In general, combination of yeast and LAB had potential at regulating inflammation of bovine mammary gland.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, study showed that adding LAB prevented E. coli infection and depressed the expression of proinflammation cytokine IL-8 and IL-1β of endometrial cells in vitro (Genis et al 2016). MPO activity is a quantitative assessment of neutrophil infiltration into mammary gland (Kan et al 2019), and our result showed that milk activity of MPO was significantly decreased by supplementation of yeast, LAB or the mixture. In general, combination of yeast and LAB had potential at regulating inflammation of bovine mammary gland.…”
Section: Discussionsupporting
confidence: 62%
“…In vitro, the application of LPS and ATP is to stimulate mMECs and to construct an in vitro mastitis model. Based on existent reports, two main interdependent processes will aggravate the mastitis inflammation: one is recruitment of inflammatory cells and the other is upregulation of proinflammatory cytokines [ 37 ]. In vivo, these experiments demonstrated that the dioscin reduces the mastitis symptoms induced by LPS in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of mastitis is high during postpartum lactation, which results in reduced breast feeding in humans and milk production in dairy animals [ 1 , 2 ]. Studies have shown that inflammation in multiple organs was associated with oxidative stress [ 5 ], but it has not been explored clearly in the mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Milk is important for the growth and development of the youth and nutrition of humans. Unfortunately, the incidence of mastitis arises during lactation, which causes severe pain and even sepsis and hinders breast feeding in humans and reduces milk production in dairy cows [ 1 , 2 ]. Gram-negative bacteria Escherichia coli is one of the main pathogens responsible for mastitis, and lipopolysaccharide (LPS) is a major component of the outer cell membranes of gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation